PENGARUH INFLASI DAN KURS TERHADAP UJRAH DALAM PEMBIAYAAN MUSYARAKAH MUTANAQISAH PADA PT. BANK MUAMALAT INDONESIA, TBK CABANG PEMATANGSIANTAR - Nuri Aslami (Universitas Islam Negeri Sumatera Utara, 2015)
This study aims to determine how the effects of inflation and exchange rate against ujrah, musyarakah, mutanaqisah PT Bank Muamalat Indonesia, Tbk Branch Pematang Siantar. This research is a field research using quantitative and qualitative approaches. The data used are secondary data, ie., data obtained from the Central Statistics Agency report, Report of Bank Indonesia, and the financial statements of PT Bank Muamalat Indonesia, Tbk Branch Pematang Siantar. The data were processed using SPSS 16. The analysis used is multiple linear regression analysis. The results showed that the inflation and the exchange rate (the independent variable) affects ujrah in Musharakah financing mutanaqisah (dependent variable). The independent variables in this study could explain the change by 3.4% and the rest (96.6%) is explained by other variables beyond the variables used. Partially, the level of significant 5% and t table of 2034, inflation and exchange rate does not significantly affect the Musharakah financing ujrah mutanaqisah. This is demonstrated by the t value inflation of 0. 489 and texchange rate of 0899.